2013
DOI: 10.1073/pnas.1217733110
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of TPP1 regulates cell cycle-dependent telomerase recruitment

Abstract: Telomere maintenance is essential for organisms with linear chromosomes and is carried out by telomerase during cell cycle. The precise mechanism by which cell cycle controls telomeric access of telomerase and telomere elongation in mammals remains largely unknown. Previous work has established oligonucleotide/oligosaccharide binding (OB) fold-containing telomeric protein TPP1, formerly known as TINT1, PTOP, and PIP1, as a key factor that regulates telomerase recruitment and activity. However, the role of TPP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…It has been shown that TPP1 undergoes post-translational modifications that affect the shelterin complex stability (21,33). Our results indicate that under conditions of oxidative stress induced by CSE, TPP1 was acetylated and possibly degraded.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that TPP1 undergoes post-translational modifications that affect the shelterin complex stability (21,33). Our results indicate that under conditions of oxidative stress induced by CSE, TPP1 was acetylated and possibly degraded.…”
Section: Discussionsupporting
confidence: 53%
“…Several studies have observed telomerase localization to telomeres specifically in S phase (Jády et al 2006;Tomlinson et al 2006), which also coincides with an increase in hTERT mRNA levels (Xi and Cech 2014). In addition, a phosphorylation site in the OB-fold domain of TPP1 (S111) could potentially aid activation of telomerase at telomeres in S, G2, and M phase (Zhang et al 2013). Introduction of mutations of S111 in different cell types has led to conflicting results.…”
Section: Telomerase Recruitment To Telomeresmentioning
confidence: 99%
“…Introduction of mutations of S111 in different cell types has led to conflicting results. In HeLa cells, it triggered telomere shortening, while expression in embryonic stem cells had no discernible effect when compared with wild-type TPP1 (Zhang et al 2013;Sexton et al 2014). Therefore, the timing of telomerase action at telomeres requires further study.…”
Section: Telomerase Recruitment To Telomeresmentioning
confidence: 99%
“…Additionally, TPP1 knockin experiments in human embryonic stem cells (hESCs) confirm that deletion of this acidic loop leads to severely shortened telomeres and reduced long-term cell viability (Sexton et al, 2014). Other TPP1 residues implicated in mediating telomerase function include: W98, which likely serves a structural role (Rao et al, 2014; Zhang et al, 2013); phosphorylation site S111, whose mutation altered telomere length regulation in cells (Zhang et al, 2013) through a mechanism not revealed in direct telomerase extension assays (Nandakumar et al, 2012); and L104, whose mutation reduces telomerase processivity but not association (Nandakumar et al, 2012) and which has been proposed to be involved in regulating telomere length homeostasis (Sexton et al, 2014). …”
Section: Introductionmentioning
confidence: 99%